Thermal-insulation low-shrinkage-rate ultraviolet in-situ curing repair material and preparation method thereof
By developing a temperature-insulating and low-shrinkage ultraviolet light in-situ curing repair material containing oligomers, diluents, photoinitiators and glass microbeads, the problem that the existing technology cannot repair large-diameter pipelines is solved, and efficient, low-noise, and low-cost pipeline repair is achieved, and good thermal loss insulation effect is achieved.
Patent Information
- Application Number
- CN202411905246.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-15
AI Technical Summary
The existing ultraviolet cured in-situ repair materials cannot effectively repair large-pipe pipes, resulting in the inability to meet the repair needs of the water supply pipeline network.
A temperature-insulated, low shrinkage-rate ultraviolet in situ curing repair material is used, which consists of oligomers, diluents, photoinitiators and glass microbeads, and is vacuum impregnated and ultraviolet cured by specific preparation methods.
This material has the advantages of low density, lightweight and low shrinkage. It can effectively repair large-diameter pipelines, improve the fit between the repaired pipeline and the original pipeline, ensure heat loss, and has the advantages of low construction noise, less cost investment, high repair efficiency, and less environmental damage.
Smart Images

Figure BDA0005204226390000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ultraviolet light in-situ curing repairing, and in particular to a temperature-insulating, low-shrinkage ultraviolet light in-situ curing repairing material and a preparation method thereof. Background Art
[0002] With the advancement of urbanization, the total length of underground water supply pipelines in my country has reached 1.0599 million kilometers. According to statistics, the service life of a large number of water supply pipelines in my country is about to reach 50 years. With the changes in the service life of pipelines and the environment around the pipes, "leakage" has become the main disease of the water supply network. In addition, due to the hidden diseases of the water supply network, road collapse accidents caused by aging, leakage and burst of pipelines occur frequently. Water supply network diseases have seriously affected the daily life of residents and the development of social economy, and may even cause major casualties and economic property losses. Therefore, the renovation of the water supply network has attracted much attention.
[0003] Ultraviolet light curing in situ repair (UV-CIPP) is a commonly used repair method. However, due to the high density and heavy weight of pipelines, the UV-curing in situ repair materials in the prior art cannot repair large-diameter pipelines.
[0004] Therefore, it is necessary to provide a temperature-insulating, low-shrinkage UV-light in-situ curing repair material and a preparation method. Summary of the invention
[0005] The purpose of the present invention is to provide a temperature-insulating, low-shrinkage ultraviolet light in-situ curing repair material and a preparation method thereof, so as to solve the problem that ultraviolet light curing in-situ repair materials in the prior art cannot repair large-diameter pipelines.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] A temperature-insulating, low-shrinkage ultraviolet light in-situ curing repair material, comprising the following components in parts by weight:
[0008] 70-90 parts of oligomer;
[0009] 10 to 30 parts of diluent;
[0010] 2 to 5 parts of photoinitiator;
[0011] Glass microspheres 0wt%~6wt%.
[0012] Further, the oligomer is bisphenol A epoxy acrylate;
[0013] The diluent is tetrahydrofuran acrylate;
[0014] The photoinitiator is 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone;
[0015] The glass microsphere is a hollow glass microsphere composed of a thermoplastic shell filled with hydrocarbon gas.
[0016] A method for preparing the temperature-insulating, low-shrinkage UV-in-situ curing repair material as described above comprises the following steps:
[0017] S1, place the beaker containing the oligomer in a heat-collecting magnetic stirrer, heat it in a water bath to 60-65°C and keep the temperature constant;
[0018] S2, adding a diluent and expandable glass microbeads to the beaker in step S1, and stirring the mixture with an electric stirrer to mix evenly;
[0019] S3, adding a photoinitiator to the mixture of step S2, and stirring the mixture with an electric stirrer to mix it evenly;
[0020] S4, placing the mixture obtained in step S3 in a vacuum negative pressure pump for 5 to 10 minutes to extract bubbles;
[0021] S5, vacuum impregnating the glass fiber cloth with the mixture obtained in step S4, and then placing it at 50mW / cm 2 The sample is irradiated and cured under ultraviolet light for 3-10 minutes, and whether the curing is complete is determined by monitoring the curing temperature. After the curing is completed, the sample is taken out of the mold to obtain the cured ultraviolet in-situ curing repair material.
[0022] Furthermore, the water bath heating in step S1 is specifically as follows: firstly, a proper amount of water is added to the DF-101S heat collecting magnetic stirrer, a beaker containing the oligomer is placed therein, and then preheated to 60-65° C. and kept at a constant temperature for a period of time until the oligomer has good fluidity.
[0023] Furthermore, in step S2 and step S3, the rotation speed of the electric stirrer when stirring the mixture is 1000-2000 rpm, and the mixing time is 3-5 minutes.
[0024] Furthermore, the extraction of bubbles in step S4 is specifically as follows: first, the beaker containing the mixture is placed into the LFDS630 digital display 220V vacuum negative pressure pump and the pump cover is closed, then the valves on both sides of the vacuum negative pressure pump are tightened, the pressure is reduced to -100psi, and finally, it is placed at a constant pressure for 5 to 10 minutes until the bubbles are completely eliminated.
[0025] Furthermore, the specific method of irradiation curing under ultraviolet light in step S5 is: at a temperature of 120°C, the resin mixture is poured into a prefabricated mold of 250mm×250mm×3mm, and then the mold is placed at a distance of 20cm from the ultraviolet lamp for ultraviolet irradiation, and the ultraviolet light power is 50mW / cm 2 , the UV irradiation time is 10min.
[0026] The present invention has the following beneficial effects:
[0027] 1. The heat-insulating, low-shrinkage UV in-situ curing repair material of the present invention has the advantages of low density, light weight, and low shrinkage. It uses UV in-situ curing to repair large-diameter pipelines with high density and self-weight, improves the fit between the repaired pipeline and the original pipeline, and ensures the heat loss of the pipeline. For pipelines with potential safety hazards, trenchless repair technology has the advantages of low construction noise, low cost investment, high repair efficiency, and less damage to the environment.
[0028] 2. The heat-insulating, low-shrinkage UV in-situ curing repair material and preparation method proposed in the present invention have reasonable configuration and are in compliance with GB5749-2022 standards after inspection. They can be used for in-situ curing repair of water supply pipes and have good mechanical properties after curing. The bending strength is 77.69-82.45 MPa, the bending modulus is 1.39-1.79 MPa, the tensile strength is 75.40-79.76 MPa, and the Barcol hardness is 27.33-28.17 Hba. DETAILED DESCRIPTION
[0029] In order to further illustrate the present invention, a temperature-insulating, low-shrinkage UV in-situ curing repair material and a preparation method provided by the present invention are described in detail below in combination with embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0030] The present invention provides a method for preparing a temperature-insulating, low-shrinkage ultraviolet light in-situ curing repair material, which comprises the following components in parts by weight:
[0031] 70-90 parts of oligomer;
[0032] 10 to 30 parts of diluent;
[0033] 2 to 5 parts of photoinitiator;
[0034] Glass microspheres 0wt%~6wt%.
[0035] Preferably, the oligomer is bisphenol A epoxy acrylate;
[0036] The diluent is tetrahydrofuran acrylate;
[0037] The photoinitiator is 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone;
[0038] Glass microspheres are hollow glass microspheres consisting of a thermoplastic shell filled with hydrocarbon gas.
[0039] A method for preparing a temperature-insulating, low-shrinkage ultraviolet light in-situ curing repair material comprises the following steps:
[0040] S1, place the beaker containing the oligomer in a heat-collecting magnetic stirrer, heat it in a water bath to 60-65°C and then keep the temperature constant. Specifically, the water bath heating is as follows: first, add an appropriate amount of water to the DF-101S heat-collecting magnetic stirrer, place the beaker containing the oligomer in it, and then preheat it to 60-65°C, and keep the temperature constant for a period of time until the oligomer has good fluidity.
[0041] S2, adding a diluent and expandable glass beads to the beaker of step S1, and stirring the mixture with an electric stirrer to mix it evenly; wherein the rotation speed of the electric stirrer when stirring the mixture is 1000-2000 rpm, and the mixing time is 3-5 minutes.
[0042] S3, adding a photoinitiator to the mixture of step S2, and stirring the mixture with an electric stirrer to mix it evenly; wherein the rotation speed of the electric stirrer when stirring the mixture is 1000-2000 rpm, and the mixing time is 3-5 minutes.
[0043] S4, the mixture obtained in step S3 is placed in a vacuum negative pressure pump for 5 to 10 minutes to extract bubbles. The specific method of extracting bubbles is as follows: first, the beaker containing the mixture is placed in a LFDS630 digital display 220V vacuum negative pressure pump and the pump cover is closed, then the valves on both sides of the vacuum negative pressure pump are tightened, the pressure is reduced to -100 psi, and finally, the mixture is placed at a constant pressure for 5 to 10 minutes until the bubbles are completely eliminated.
[0044] S5, vacuum impregnating the glass fiber cloth with the mixture obtained in step S4, and then placing it at 50mW / cm 2 The curing is carried out under ultraviolet light for 3-10 minutes, and the curing temperature is monitored to determine whether the curing is complete. After the curing is completed, the sample is taken out of the mold to obtain the cured ultraviolet light in-situ curing repair material. The specific method of curing under ultraviolet light is as follows: at a temperature of 120°C, the resin mixture is poured into a prefabricated mold of 250mm×250mm×3mm, and then the mold is placed at a distance of 20cm from the ultraviolet light for ultraviolet light irradiation, the ultraviolet light power is 50mW / cm2, and the ultraviolet light irradiation time is 10min.
[0045] The heat-insulating, low-shrinkage UV-light in-situ curing repair material of the present invention has the advantages of low density, light weight, and low shrinkage. It uses UV-light in-situ curing to repair large-diameter pipelines with high density and self-weight, thereby improving the fit between the repaired pipeline and the original pipeline and ensuring the heat loss of the pipeline. For pipelines with potential safety hazards, trenchless repair technology has the advantages of low construction noise, low cost investment, high repair efficiency, and less damage to the environment.
[0046] Example 1
[0047] The temperature-insulating, low-shrinkage UV in-situ curing repair material of this embodiment comprises the following components in parts by weight:
[0048] Oligomer 80 parts
[0049] 20 parts of diluent
[0050] 2 parts of photoinitiator
[0051] Glass microspheres 0wt%
[0052] The oligomer is bisphenol A epoxy acrylate, the diluent is tetrahydrofuran acrylate, the photoinitiator is 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, and the glass microbeads are composed of a thermoplastic shell filled with hydrocarbon gas.
[0053] The preparation method comprises the following steps:
[0054] S1, put the beaker containing the oligomer into the heat collecting magnetic stirrer, heat it in a water bath to 60-65°C and keep the temperature constant. The water bath heating includes first adding an appropriate amount of water to the DF-101S heat collecting magnetic stirrer, putting the beaker containing the oligomer into it, and then preheating it to 60-65°C, and then keeping the temperature constant for a period of time until the oligomer has good fluidity.
[0055] S2, adding a diluent and expandable glass microspheres into the beaker of step S1, and stirring the mixture with an electric stirrer; wherein the rotation speed of the electric stirrer is 1000-2000 rpm, and the mixing time is 3-5 minutes.
[0056] S3, adding a photoinitiator to the mixture of step S2, and stirring the mixed solution with an electric stirrer to mix it evenly; wherein the speed of the electric stirrer is 1000-2000 rpm, and the mixing time is 3-5 minutes.
[0057] S4, the mixture obtained in step S3 is placed in a vacuum negative pressure pump for 5 to 10 minutes to extract bubbles. The extraction of bubbles includes first placing the beaker containing the mixture into a LFDS630 digital display 220V vacuum negative pressure pump and covering it with a lid, then tightening the valves on both sides, reducing the pressure to -100 psi, and finally placing it at a constant pressure for 5 to 10 minutes until the bubbles are completely eliminated.
[0058] S5, vacuum impregnate the glass fiber cloth with the mixture obtained in step S4, and then place it under a 50mW / cm2 ultraviolet lamp for irradiation curing for 3-10min. The specific method of ultraviolet curing is: at a temperature of 120°C, pour the mixture into a prefabricated mold of 250mm×250mm×3mm, and then place the mold at a distance of 20cm from the ultraviolet lamp for ultraviolet irradiation, the ultraviolet power is 50mW / cm2, and the ultraviolet irradiation time is 10min. By monitoring the curing temperature, it is determined whether the curing is completed. After the curing is completed, the sample is taken out of the mold to obtain the cured ultraviolet light in-situ curing repair material.
[0059] Example 2
[0060] The temperature-insulating, low-shrinkage UV in-situ curing repair material of this embodiment comprises the following components in parts by weight:
[0061] Oligomer 80 parts
[0062] 20 parts of diluent
[0063] 3 parts of photoinitiator
[0064] Glass beads 1wt%
[0065] The oligomer is bisphenol A epoxy acrylate, the diluent is tetrahydrofuran acrylate, the photoinitiator is 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, and the glass microbeads are composed of a thermoplastic shell filled with hydrocarbon gas.
[0066] The preparation method comprises the following steps:
[0067] S1, put the beaker containing the oligomer into the heat collecting magnetic stirrer, heat it in a water bath to 60-65°C and keep the temperature constant. The water bath heating includes first adding an appropriate amount of water to the DF-101S heat collecting magnetic stirrer, putting the beaker containing the oligomer into it, and then preheating it to 60-65°C, and then keeping the temperature constant for a period of time until the oligomer has good fluidity.
[0068] S2, adding a diluent and expandable glass microspheres into the beaker of step S1, and stirring the mixture with an electric stirrer; wherein the rotation speed of the electric stirrer is 1000-2000 rpm, and the mixing time is 3-5 minutes.
[0069] S3, adding a photoinitiator to the mixture of step S2, and stirring the mixed solution with an electric stirrer to mix it evenly; wherein the speed of the electric stirrer is 1000-2000 rpm, and the mixing time is 3-5 minutes.
[0070] S4, the mixture obtained in step S3 is placed in a vacuum negative pressure pump for 5 to 10 minutes to extract bubbles. The extraction of bubbles includes first placing the beaker containing the mixture into a LFDS630 digital display 220V vacuum negative pressure pump and covering it with a lid, then tightening the valves on both sides, reducing the pressure to -100 psi, and finally placing it at a constant pressure for 5 to 10 minutes until the bubbles are completely eliminated.
[0071] S5, vacuum impregnating the glass fiber cloth with the mixture obtained in step S4, and then placing it at 50mW / cm 2 The mixture was poured into a prefabricated mold of 250 mm × 250 mm × 3 mm at a temperature of 120 ° C, and then the mold was placed 20 cm away from the UV lamp for UV irradiation. The UV power was 50 mW / cm 2 The UV irradiation time is 10 minutes. Whether the curing is completed is determined by monitoring the curing temperature. After the curing is completed, the sample is taken out of the mold to obtain the cured UV in-situ curing repair material.
[0072] Example 3
[0073] The temperature-insulating, low-shrinkage UV in-situ curing repair material of this embodiment comprises the following components in parts by weight:
[0074] Oligomer 80 parts
[0075] 20 parts of diluent
[0076] Photoinitiator 4 parts
[0077] Glass microspheres 2wt%
[0078] The oligomer is bisphenol A epoxy acrylate, the diluent is tetrahydrofuran acrylate, the photoinitiator is 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, and the glass microbeads are composed of a thermoplastic shell filled with hydrocarbon gas.
[0079] The preparation method comprises the following steps:
[0080] S1, put the beaker containing the oligomer into the heat collecting magnetic stirrer, heat it in a water bath to 60-65°C and keep the temperature constant. The water bath heating includes first adding an appropriate amount of water to the DF-101S heat collecting magnetic stirrer, putting the beaker containing the oligomer into it, and then preheating it to 60-65°C, and then keeping the temperature constant for a period of time until the oligomer has good fluidity.
[0081] S2, adding a diluent and expandable glass microspheres into the beaker of step S1, and stirring the mixture with an electric stirrer; wherein the rotation speed of the electric stirrer is 1000-2000 rpm, and the mixing time is 3-5 minutes.
[0082] S3, adding a photoinitiator to the mixture of step S2, and stirring the mixed solution with an electric stirrer to mix it evenly; wherein the speed of the electric stirrer is 1000-2000 rpm, and the mixing time is 3-5 minutes.
[0083] S4, the mixture obtained in step S3 is placed in a vacuum negative pressure pump for 5 to 10 minutes to extract bubbles. The extraction of bubbles includes first placing the beaker containing the mixture into a LFDS630 digital display 220V vacuum negative pressure pump and covering it with a lid, then tightening the valves on both sides, reducing the pressure to -100 psi, and finally placing it at a constant pressure for 5 to 10 minutes until the bubbles are completely eliminated.
[0084] S5, vacuum impregnating the glass fiber cloth with the mixture obtained in step S4, and then placing it at 50mW / cm 2 The mixture was poured into a prefabricated mold of 250 mm × 250 mm × 3 mm at a temperature of 120 ° C, and then the mold was placed 20 cm away from the UV lamp for UV irradiation. The UV power was 50 mW / cm 2 The UV irradiation time is 10 minutes. Whether the curing is completed is determined by monitoring the curing temperature. After the curing is completed, the sample is taken out of the mold to obtain the cured UV in-situ curing repair material.
[0085] Example 4
[0086] The temperature-insulating, low-shrinkage UV-curable in-situ repair material of this embodiment comprises the following components in parts by weight:
[0087] Oligomer 80 parts
[0088] 20 parts of diluent
[0089] 2 parts of photoinitiator
[0090] Glass microspheres 3wt%
[0091] The oligomer is bisphenol A epoxy acrylate, the diluent is tetrahydrofuran acrylate, the photoinitiator is 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, and the glass microbeads are composed of a thermoplastic shell filled with hydrocarbon gas.
[0092] The preparation method comprises the following steps:
[0093] S1, put the beaker containing the oligomer into the heat collecting magnetic stirrer, heat it in a water bath to 60-65°C and keep the temperature constant. The water bath heating includes first adding an appropriate amount of water to the DF-101S heat collecting magnetic stirrer, putting the beaker containing the oligomer into it, and then preheating it to 60-65°C, and then keeping the temperature constant for a period of time until the oligomer has good fluidity.
[0094] S2, adding a diluent and expandable glass microspheres into the beaker of step S1, and stirring the mixture with an electric stirrer; wherein the rotation speed of the electric stirrer is 1000-2000 rpm, and the mixing time is 3-5 minutes.
[0095] S3, adding a photoinitiator to the mixture of step S2, and stirring the mixed solution with an electric stirrer to mix it evenly; wherein the speed of the electric stirrer is 1000-2000 rpm, and the mixing time is 3-5 minutes.
[0096] S4, the mixture obtained in step S3 is placed in a vacuum negative pressure pump for 5 to 10 minutes to extract bubbles. The extraction of bubbles includes first placing the beaker containing the mixture into a LFDS630 digital display 220V vacuum negative pressure pump and covering it with a lid, then tightening the valves on both sides, reducing the pressure to -100 psi, and finally placing it at a constant pressure for 5 to 10 minutes until the bubbles are completely eliminated.
[0097] S5, vacuum impregnating the glass fiber cloth with the mixture obtained in step S4, and then placing it at 50mW / cm 2 The mixture was poured into a prefabricated mold of 250 mm × 250 mm × 3 mm at a temperature of 120 ° C, and then the mold was placed 20 cm away from the UV lamp for UV irradiation. The UV power was 50 mW / cm 2 The UV irradiation time is 10 minutes. Whether the curing is completed is determined by monitoring the curing temperature. After the curing is completed, the sample is taken out of the mold to obtain the cured UV in-situ curing repair material.
[0098] Example 5
[0099] The temperature-insulating, low-shrinkage UV-curable in-situ repair material of this embodiment comprises the following components in parts by weight:
[0100] Oligomer 80 parts
[0101] 20 parts of diluent
[0102] 2 parts of photoinitiator
[0103] Glass beads 4wt%
[0104] The oligomer is bisphenol A epoxy acrylate, the diluent is tetrahydrofuran acrylate, the photoinitiator is 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, and the glass microbeads are composed of a thermoplastic shell filled with hydrocarbon gas.
[0105] The preparation method comprises the following steps:
[0106] S1, put the beaker containing the oligomer into the heat collecting magnetic stirrer, heat it in a water bath to 60-65°C and keep the temperature constant. The water bath heating includes first adding an appropriate amount of water to the DF-101S heat collecting magnetic stirrer, putting the beaker containing the oligomer into it, and then preheating it to 60-65°C, and then keeping the temperature constant for a period of time until the oligomer has good fluidity.
[0107] S2, adding a diluent and expandable glass microspheres into the beaker of step S1, and stirring the mixture with an electric stirrer; wherein the rotation speed of the electric stirrer is 1000-2000 rpm, and the mixing time is 3-5 minutes.
[0108] S3, adding a photoinitiator to the mixture of step S2, and stirring the mixed solution with an electric stirrer to mix it evenly; wherein the speed of the electric stirrer is 1000-2000 rpm, and the mixing time is 3-5 minutes.
[0109] S4, the mixture obtained in step S3 is placed in a vacuum negative pressure pump for 5 to 10 minutes to extract bubbles. The extraction of bubbles includes first placing the beaker containing the mixture into a LFDS630 digital display 220V vacuum negative pressure pump and covering it with a lid, then tightening the valves on both sides, reducing the pressure to -100 psi, and finally placing it at a constant pressure for 5 to 10 minutes until the bubbles are completely eliminated.
[0110] S5, vacuum impregnating the glass fiber cloth with the mixture obtained in step S4, and then placing it at 50mW / cm 2 The mixture was poured into a prefabricated mold of 250 mm × 250 mm × 3 mm at a temperature of 120 ° C, and then the mold was placed 20 cm away from the UV lamp for UV irradiation. The UV power was 50 mW / cm 2The UV irradiation time is 10 minutes. Whether the curing is completed is determined by monitoring the curing temperature. After the curing is completed, the sample is taken out of the mold to obtain the cured UV in-situ curing repair material.
[0111] Example 6
[0112] The temperature-insulating, low-shrinkage UV in-situ curing repair material of this embodiment comprises the following components in parts by weight:
[0113] Oligomer 80 parts
[0114] 20 parts of diluent
[0115] 2 parts of photoinitiator
[0116] Glass microspheres 5wt%
[0117] The oligomer is bisphenol A epoxy acrylate, the diluent is tetrahydrofuran acrylate, the photoinitiator is 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, and the glass microbeads are composed of a thermoplastic shell filled with hydrocarbon gas.
[0118] The preparation method comprises the following steps:
[0119] S1, put the beaker containing the oligomer into the heat collecting magnetic stirrer, heat it in a water bath to 60-65°C and keep the temperature constant. The water bath heating includes first adding an appropriate amount of water to the DF-101S heat collecting magnetic stirrer, putting the beaker containing the oligomer into it, and then preheating it to 60-65°C, and then keeping the temperature constant for a period of time until the oligomer has good fluidity.
[0120] S2, adding a diluent and expandable glass microspheres into the beaker of step S1, and stirring the mixture with an electric stirrer; wherein the rotation speed of the electric stirrer is 1000-2000 rpm, and the mixing time is 3-5 minutes.
[0121] S3, adding a photoinitiator to the mixture of step S2, and stirring the mixed solution with an electric stirrer to mix it evenly; wherein the speed of the electric stirrer is 1000-2000 rpm, and the mixing time is 3-5 minutes.
[0122] S4, the mixture obtained in step S3 is placed in a vacuum negative pressure pump for 5 to 10 minutes to extract bubbles. The extraction of bubbles includes first placing the beaker containing the mixture into a LFDS630 digital display 220V vacuum negative pressure pump and covering it with a lid, then tightening the valves on both sides, reducing the pressure to -100 psi, and finally placing it at a constant pressure for 5 to 10 minutes until the bubbles are completely eliminated.
[0123] S5, vacuum impregnating the glass fiber cloth with the mixture obtained in step S4, and then placing it at 50mW / cm 2 The mixture was poured into a prefabricated mold of 250 mm × 250 mm × 3 mm at a temperature of 120 ° C, and then the mold was placed 20 cm away from the UV lamp for UV irradiation. The UV power was 50 mW / cm 2 The UV irradiation time is 10 minutes. Whether the curing is completed is determined by monitoring the curing temperature. After the curing is completed, the sample is taken out of the mold to obtain the cured UV in-situ curing repair material.
[0124] Example 7
[0125] The temperature-insulating, low-shrinkage UV-curable in-situ repair material of this embodiment comprises the following components in parts by weight:
[0126] Oligomer 80 parts
[0127] 20 parts of diluent
[0128] 2 parts of photoinitiator
[0129] Glass microspheres 6wt%
[0130] The oligomer is bisphenol A epoxy acrylate, the diluent is tetrahydrofuran acrylate, the photoinitiator is 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone, and the glass microbeads are composed of a thermoplastic shell filled with hydrocarbon gas.
[0131] The preparation method comprises the following steps:
[0132] S1, put the beaker containing the oligomer into the heat collecting magnetic stirrer, heat it in a water bath to 60-65°C and keep the temperature constant. The water bath heating includes first adding an appropriate amount of water to the DF-101S heat collecting magnetic stirrer, putting the beaker containing the oligomer into it, and then preheating it to 60-65°C, and then keeping the temperature constant for a period of time until the oligomer has good fluidity.
[0133] S2, adding a diluent and expandable glass microspheres into the beaker of step S1, and stirring the mixture with an electric stirrer; wherein the rotation speed of the electric stirrer is 1000-2000 rpm, and the mixing time is 3-5 minutes.
[0134] S3, adding a photoinitiator to the mixture of step S2, and stirring the mixed solution with an electric stirrer to mix it evenly; wherein the speed of the electric stirrer is 1000-2000 rpm, and the mixing time is 3-5 minutes.
[0135] S4, the mixture obtained in step S3 is placed in a vacuum negative pressure pump for 5 to 10 minutes to extract bubbles. The extraction of bubbles includes first placing the beaker containing the mixture into a LFDS630 digital display 220V vacuum negative pressure pump and covering it with a lid, then tightening the valves on both sides, reducing the pressure to -100 psi, and finally placing it at a constant pressure for 5 to 10 minutes until the bubbles are completely eliminated.
[0136] S5, vacuum impregnating the glass fiber cloth with the mixture obtained in step S4, and then placing it at 50mW / cm 2 The mixture was poured into a prefabricated mold of 250 mm × 250 mm × 3 mm at a temperature of 120 ° C, and then the mold was placed 20 cm away from the UV lamp for UV irradiation. The UV power was 50 mW / cm 2 The UV irradiation time is 10 minutes. Whether the curing is completed is determined by monitoring the curing temperature. After the curing is completed, the sample is taken out of the mold to obtain the cured UV in-situ curing repair material.
[0137] The present invention aims to provide a temperature-insulating, low-shrinkage ultraviolet light in-situ curing repair material and a preparation method thereof, wherein each component of the ultraviolet light in-situ curing material meets the standards after inspection, can be used for in-situ curing repair of water supply pipes, and has a good temperature-insulating effect after curing.
[0138] The performance test of the heat-insulating, low-shrinkage UV in-situ curing repair materials of Examples 1-7 was carried out, and the test results are shown in Table 1 below:
[0139]
[0140] Table 1
[0141] It can be seen from the data in the above table that the temperature-insulating, low-shrinkage UV in-situ curing repair material prepared in Example 7 is more excellent in thermal conductivity, tensile properties, water absorption and shrinkage than those in Examples 1, 2, 3, 4, 5 and 6.
[0142] The invention proposes a temperature-insulating, low-shrinkage ultraviolet in-situ curing repair material and a preparation method, which have reasonable configuration, meet the GB5749-2022 standard after inspection, can be used for in-situ curing repair of large-diameter water supply pipes, and have good mechanical properties after curing, with a bending strength of 77.69-82.45 MPa, a bending modulus of 1.39-1.79 MPa, a tensile strength of 75.40-79.76 MPa, and a Barcol hardness of 27.33-28.17 Hba.
[0143] In summary, the temperature-insulating, low-shrinkage UV in-situ repair material and its preparation method obtained in the present application can meet the requirements of UV-curing in-situ repair of large-diameter pipelines in a low-temperature environment.
[0144] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A temperature-insulating, low-shrinkage UV-curable in-situ repair material, characterized in that: In parts by weight, it includes the following components: 70-90 parts of oligomer; 10 to 30 parts of diluent; 2 to 5 parts of photoinitiator; Glass microspheres 0wt%~6wt%.
2. The temperature-insulating, low-shrinkage UV-in-situ curing repair material according to claim 1, characterized in that: The oligomer is bisphenol A epoxy acrylate; The diluent is tetrahydrofuran acrylate; The photoinitiator is 2-hydroxy-4-(2-hydroxyethoxy)-2-methylpropiophenone; The glass microsphere is a hollow glass microsphere composed of a thermoplastic shell filled with hydrocarbon gas.
3. A method for preparing a temperature-insulating, low-shrinkage UV-in-situ curing repair material according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1, place the beaker containing the oligomer in a heat-collecting magnetic stirrer, heat it in a water bath to 60-65°C and keep the temperature constant; S2, adding a diluent and expandable glass microbeads to the beaker in step S1, and stirring the mixture with an electric stirrer to mix evenly; S3, adding a photoinitiator to the mixture of step S2, and stirring the mixture with an electric stirrer to mix it evenly; S4, placing the mixture obtained in step S3 in a vacuum negative pressure pump for 5 to 10 minutes to extract bubbles; S5, vacuum impregnating the glass fiber cloth with the mixture obtained in step S4, and then placing it at 50mW / cm 2 The sample is irradiated and cured under ultraviolet light for 3-10 minutes, and whether the curing is complete is determined by monitoring the curing temperature. After the curing is completed, the sample is taken out of the mold to obtain the cured ultraviolet in-situ curing repair material.
4. The method for preparing the temperature-insulating, low-shrinkage UV-in-situ curing repair material according to claim 3, characterized in that: The water bath heating in step S1 is specifically as follows: firstly, add a proper amount of water to the DF-101S heat collecting magnetic stirrer, put the beaker containing the oligomer into it, and then preheat to 60-65° C. and keep the temperature constant for a period of time until the oligomer has good fluidity.
5. The method for preparing the temperature-insulating, low-shrinkage UV-in-situ curing repair material according to claim 3, characterized in that: In step S2 and step S3, the electric stirrer stirs the mixture at a speed of 1000-2000 rpm, and the mixing time is 3-5 minutes.
6. The method for preparing the temperature-insulating, low-shrinkage UV-in-situ curing repair material according to claim 3, characterized in that: The extraction of bubbles in step S4 is specifically as follows: first, the beaker containing the mixture is placed into the LFDS630 digital display 220V vacuum negative pressure pump and the pump cover is closed, then the valves on both sides of the vacuum negative pressure pump are tightened, the pressure is reduced to -100psi, and finally, a constant pressure is placed for 5 to 10 minutes until the bubbles are completely eliminated.
7. The method for preparing the temperature-insulating, low-shrinkage UV-in-situ curing repair material according to claim 3, characterized in that: The specific method of irradiation curing under ultraviolet light in step S5 is: at a temperature of 120°C, the resin mixture is poured into a prefabricated mold of 250mm×250mm×3mm, and then the mold is placed at a distance of 20cm from the ultraviolet lamp for ultraviolet irradiation, and the ultraviolet light power is 50mW / cm 2 , the UV irradiation time is 10min.
Citation Information
Patent Citations
UV cured repairing material and preparation method thereof
CN106675484A
Environment-friendly ultraviolet curing resin as well as preparation method and application thereof
CN118530414A